God is my adventure - "Landau, Rom" (London, 1935)
This book is the confession of an adventure and the story of friendship with those men whom a future generation may possibly call the true prophets of our time. The core of the adventure is a search for God. I leave it to the reader to decide whether such a search can be sacrilegious.
Keywords: "Philosophy, Medieval"